208k views
5 votes
Which equation is equivalent to -2(2 − 2x) = 4 − 8(1 − x)?

User Jicaar
by
5.1k points

2 Answers

3 votes

Answer: 0

Explanation:

User Stijn Geukens
by
5.7k points
5 votes

Answer:

x = 0

Explanation:

-2(2 − 2x) = 4 − 8(1 − x)

Apply the distributive property:

−2(2 − 2x) = 4 − 8(1 − x)

(−2)(2) + (−2)(−2x) = 4 + (−8)(1) + (−8)(−x)

−4 + 4x = 4 + (−8) + 8x

Combine like terms:

4x − 4 = (8x) + (4+−8)

4x − 4 = 8x + (−4)

4x − 4 = 8x − 4

Subtract 8x from both sides:

4x − 4 − 8x = 8x − 4 − 8x

−4x − 4 = −4

Add 4 to both sides:

−4x − 4 + 4= −4 + 4

−4x = 0

Divide both sides by -4:

-4x/-4 = 0/-4

x = 0

User Arkiliknam
by
5.5k points